Numerical Study on the Screening Performance of a Cylindrical Vibrating Screen with Coupled Rotation and Vibration - Li, Yujia; Xia, Yu; Ren, Tao; Zhuang, Weiye; Jin, Zheyi; Yu, Weisong; Huang, Xiao (International Journal of Mechanical and Electrical Engineering, 2025)
Advancements in drilling technology and the increasing demand for complex drilling fluids have revealed the limitations of conventional solid control systems, driving the need for innovation. This paper proposes a cylindrical vibrating screen with coupled rotation and vibration, which improves solid-liquid screening efficiency and large particle agglomeration compared to traditional planar screens. The efficiency of a vibrating screen depends on factors such as frequency, rotational speed, amplitude, and inclination angle, making optimization of these parameters critical for enhancing industrial production efficiency. Using the Discrete Element Method (DEM), this study simulates wet and dry particle screening on a cylindrical vibrating screen. It evaluates particle screening efficiency, collision frequency, and particle distribution across 30 different vibration parameter combinations. The analysis identifies the optimal settings for frequency, amplitude, speed, and inclination angle under various conditions. The optimal combination was found to be an amplitude of 4 mm, frequency of 15 Hz, rotational speed of 10 rpm, and a screen inclination angle of 0°. Screening efficiency is higher when particles exhibit an arithmetic distribution on the screen. This study provides valuable insights for the efficient operation and optimal design of cylindrical vibrating screens.